Towards a tool for design ideation: Insights from use of SketchStorm - Lindley, Siân; Cao, Xiang; Helmes, John; Morris, Richard; Meek, Sam (Proceedings of the 27th BCS conference on Human Computer Interaction, 2013)
We present findings from a deployment of SketchStorm, a tool for designers that supports sketch in a central canvas, whilst streaming images relating to a search query around the periphery. Our overarching goal was to explore the potential for combining sketching and use of examples, two activities that are associated with design ideation. Initial interviews with designers suggested that a tool that supports encounters with non-designerly content, that supports awareness of what has already been collected, and that allows this content to be laid out, manipulated, and integrated into the process of working out of ideas, would be of value. A month-long deployment allowed us to examine these ideas in more depth, through ‘research through prototypes in practice’ (Keller et al., 2009). Our findings highlight two ways in which web-based images can be utilised. On the one hand, they can serve as examples and, where this is the case, encounters with them should be rich and memorable, and tools should support a range of actions such as triaging, annotation, and manipulation. On the other hand, images can be used to create a backdrop to on-going activity, so as to underpin serendipitous encounters. Where this is the case, enabling designers to engineer these encounters, so that they are framed by moments of idleness and latent goals, is key.